Lanthanide separation using size-selective crystallization of Ln-MOFs. Issue 42 (11th May 2017) - Ya Gao, Heng; Li Peng, Wen; Pan Meng, Pan; Feng Feng, Xue; Qiang Li, Jian; Qiong Wu, Hui; Sheng Yan, Chang; Yang Xiong, Yang; Luo, Feng
Abstract : We report herein an elaborate method, size-selective crystallization of Ln-MOFs, to isolate lanthanide (Ln) ions. Abstract : Herein, we report an elaborate method, size-selective crystallization of Ln-MOFs, to isolate lanthanide (Ln) ions. Herein, 13 lanthanide ions, except for the radioactive Pm(iii ) ion, were separated by four types of Ln-MOFs: type I (La–Pr), type II (Nd–Eu), type III (Gd–Ho), and type IV (Er–Lu). Further systemic investigation also suggested the highly selective separation of lanthanide ions by this method.